Revealing the secrets of the Jews: Johannes Pfefferkorn and Christian Writings about Jewish life and literature in early modern Europe - Adams, Jonathan; Heß, Cordelia (De Gruyter, 2017)
"In this volume, scholars of history, literature, art and theology re-evaluate the context and significance of polemical and ethnographic literature about Jews by Johannes Pfefferkorn and other converts. The volume presents new perspectives on the life and works of Pfefferkorn, the sixteenth-century debate about Jewish books, the sources for anti-Jewish writing, and the interconnection between early modern ethnography and anti-Jewish polemics"--